Pendidikan Jihad Menurut Imam Bukhari (Studi Naskah Hadits-Hadits Kitab al Jihad Dalam Shahih Bukhari) - Al-Hamat, Anung; Mujahidin, Endin; Tamam, Abas Mansur; Hafidhuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2016)
There are two mistaken blocks in looking upon the essence of the holy war that apparently influence the religious and social life. It implies that there is a group that sees sarcastically to the terminology of the holy war even there is one that tries to eliminate from the Islamic Shari’a. On the other hand, it appears a group that behaves in extreme way and sees the holy war in narrow outlook, that is war. This is the importance of propagating the education of the holy war with the right way referring to the authoritative Islamic scholars. This research focuses on the holy war education of Imam Bukhari by studying chapters and hadiths arranged in the book of the holy war in his shahih book. So that it can be known how the idea of Imam Bukhari in the holy war education with the focus on four education components, those are goal, program, method and evaluation then how the implementation in the contemporary world of education. According to the Title of the research, so the kind of research used is the library research. The library research is a research which is carried out both with literature and non-literature. Among the samples of literature are books, notes, or the report of research from previous researches. As for the samples of non-literature, such as audio record and visual record. This research reveals the finding of the Imam Bukhari’s holy war education that consists of goals those are related to the urgency of aqeedah, morals (akhlaq), the wide meaning of the holy war, and the urgency of healthe body. The Material of Aqeedah related faith, obedient, sincere, receive (tawakal), love, scare,and hope to Allah. The Materials of morals (akhlaq), such as patience, honesty, enthusiastic in doing war, courage, genorosity, keeping promise, compassionate, modesty (tawadhu’), wisdom, and avoiding evil character. The spiritual Material such as cumpolsory prayer (shalat), sunnah prayer, fasting, pray,reciting Al-Qur’an, saying takbeer, tahlil, and tasbih. The Physical Material such as keeping body hygiene, protecting and caring of body in order not to get wound, keeping physical hygiene by treating wound, keeping stamina and body hygiene by consuming good food and doing exercises before war. The methods applied are not less than 20 methods. And the evaluation by considering the quantity and the power of soldiers, security condition, preparing reserve commander, the couse of loss, joining in the holy war and administering sanctions. The ide of Imam Bukhari in the holy war education is very comprehensive, effective, and aplicative. So it is important to study his idea so that the comprehension of the holy war conception can be comprehensive and unimpaired. And it is possible, that the thing discovered in the research would be implemented in the world of education and can be used as one of referrence in learning. Keyword: jihad education, library research, Shahih Bukhari